Den russiske haldninga til Barentssamarbeidet 2000 - 2008 - Svanes, Kristian (The University of Bergen, 2009)
The main objective of this Master Thesis was to examine the Russian attitude to the Barents Cooperation from 2000 to 2008. This was accomplished by taking a closer look at the federal and regional Russian attitude, mainly by analysing articles, interviews and speeches published by the Russian MFA, minute books published by the Barents Regional Council and Committee and interviews with informants based in Northwest Russia. I attempted to discover a link between the centralisation of state power during the presidency of Vladimir Putin and the regional Russian attitude towards the Barents Cooperation (BC). The federal authorities expressed a negative experiences with the cooperation progress in the period of 2000-2002, while at the same experiencing weak influence regarding EU's Northern Dimension. From 2003-2008 the federal authorities signalled a more positive attitude towards the BC. I found that the federal authorities focused heavily on the economic part of the BC in the period of 2000-2003, subsequently, however, this approach changed to a broader one between 2004 and 2008. The prominent focus on the economic part was linked to President Putin urging the MFA in 2001 to focus on promoting Russian economic interests and the great gap in living standards between the Russian and Nordic side. The environmental component was also perceived as one of high priority. This can be explained as a strategy for attracting additional finances to the, in addition the economic benefits increased energy efficiency provides. The regional priorities to a large degree corresponded with the federal. Regional Minute books revealed that the regional level of meeting attendance increased substantially during the period, implying that also the regional attitude was more positive in 2008 than in 2003. However, the Russian regions were significantly less active compared to their Nordic counterparts. More cooperation experience, a more effective BC and improved economic conditions in the Russian Federation contributed to the more ...